COVID-19 and cochleovestibular disorders: A review - Andrey Yu. Ovchinnikov; Nina A. Miroshnichenko; Kristina V. Savranskaya; Andrey A. Zaitsev (ZAO "Consilium Medicum", 2023)
COVID-19 is an urgent problem for healthcare in various countries of the world, as it is characterized by high rates of morbidity and mortality, and is also accompanied by a wide range of complications. These include smell and taste disorders, cochleovestibular disorders and delayed neurological disorders. The purpose of this article is to describe the audiovestibular disorders associated with novel COVID-19 infection, including possible side effects of ototoxicity associated with the use of drugs used in treatment protocols for this disease.